Firms, Breach of Norms, and Reputation Damage. Issue 6 (July 2019) - Breitinger, Dominik; Bonardi, Jean-Philippe
A large body of literature looks at how firms develop and maintain their reputation. Little is known, however, about factors leading to a damaged corporate reputation. In this article, the authors compare two sets of predictors of reputational damage following a reported breach of norms: the characteristics of the breach and the characteristics of the actor reporting the breach. Theoretically, the authors argue that the latter is likely to prevail over the former. The authors test this proposition in the highly normative context of corporate social responsibility (CSR). Building on a global data set of over 8, 600 CSR-related norm breaches, directed against 451 firms on the Fortune ranking reputation over the 2006-2009 period, the authors find empirical support for the idea that reputation damage is not really driven by the severity and novelty of the allegation, but by the type of source reporting the issue as well as the credibility of this source. Hence, these results lend some support to a socially constructed view of reputational damage, in which being portrayed by prominent actors as deviating from the norm is more important than the actual deviation from the goal of the norm itself.